2018
DOI: 10.1111/cogs.12579
|View full text |Cite
|
Sign up to set email alerts
|

Karma or Immortality: Can Religion Influence Space‐Time Mappings?

Abstract: People implicitly associate the "past" and "future" with "front" and "back" in their minds according to their cultural attitudes toward time. As the temporal focus hypothesis (TFH) proposes, future-oriented people tend to think about time according to the future-in-front mapping, whereas past-oriented people tend to think about time according to the past-in-front mapping (de la Fuente, Santiago, Román, Dumitrache, & Casasanto, 2014). Whereas previous studies have demonstrated that culture exerts an important i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
0
17
1
Order By: Relevance
“…Indeed, some recent studies have shown that individuals' temporal focus and the corresponding space–time mappings are also affected by such factors, as whether one is pregnant, whether one's religious belief is Buddhism or Taoism, and whether the temporal diagram task is conducted at the beginning of a new year or on the Tomb Sweeping Day, etc. (Li & Cao, , , ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, some recent studies have shown that individuals' temporal focus and the corresponding space–time mappings are also affected by such factors, as whether one is pregnant, whether one's religious belief is Buddhism or Taoism, and whether the temporal diagram task is conducted at the beginning of a new year or on the Tomb Sweeping Day, etc. (Li & Cao, , , ).…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study, Bylund et al (2019), even failed to find evidence at a cross-cultural level. (Li & Cao, 2018a, 2018b, 2018c. Thus, it appears that the significant relationship between temporal-focus and sagittal space-time mappings may not be found in some cases.…”
Section: Future Pastmentioning
confidence: 98%
See 2 more Smart Citations
“…At the intermediate level of analysis, temporal focus seems to account for individual variation within cultures, as seen in differences in mappings associated with pregnancy, age, and circadian rhythm (de la Fuente et al, 2014; Li, 2018; Li & Cao, 2018b). Finally, at the finest level of analysis, that of moment-to-moment variability within individuals, changes induced in temporal focus have been reported to trigger corresponding changes in front–back mappings (de la Fuente et al, 2014; Li & Cao, 2018a).…”
mentioning
confidence: 99%